2022
DOI: 10.1186/s12877-021-02721-w
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between non-alcoholic fatty liver disease and cognitive function? A systematic review

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) is represented as the most common liver disease worldwide. NAFLD is associated with metabolic risk factors underpinned by insulin resistance, inflammation and endothelial dysfunction, leading to extrahepatic changes in central nervous diseases such as cognitive impairment, Alzheimer’s disease and dementia. The aim of the review is to explore the association between NAFLD and cognitive function. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 43 publications
1
27
0
1
Order By: Relevance
“…The conclusions drawn from the results of the data can also be verified from the results of previous research. A review (George et al, 2022 ) of 11 observational studies showed NAFLD to be associated with low cognitive ability across several domains, such as “general cognition,” “mental speed, attention, and psychomotor speed,” and “ideas, abstraction, figural creations, and mental flexibility.” In the study by Sang et al (Seo et al, 2016 ), 874 (19.5%) of 4,472 patients with confirmed NAFLD were diagnosed with cognitive impairment. However, the study failed to provide enough data to calculate the increased risk of cognitive impairment in relation to NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusions drawn from the results of the data can also be verified from the results of previous research. A review (George et al, 2022 ) of 11 observational studies showed NAFLD to be associated with low cognitive ability across several domains, such as “general cognition,” “mental speed, attention, and psychomotor speed,” and “ideas, abstraction, figural creations, and mental flexibility.” In the study by Sang et al (Seo et al, 2016 ), 874 (19.5%) of 4,472 patients with confirmed NAFLD were diagnosed with cognitive impairment. However, the study failed to provide enough data to calculate the increased risk of cognitive impairment in relation to NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that NAFLD is associated with poorer cognitive function. Nonetheless, the studies conducted to date have been limited to an observational design and have demonstrated methodological heterogeneity, using various diagnostic tools to assess cognitive function (George et al, 2022 ). Meanwhile, systematic reviews and meta-analyses concerning the association between NAFLD and cognitive impairment or dementia are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Приходько «Влияние орнитина аспартата и эмпаглифлозина на проявления мнестического дефицита при экспериментальном стеатогепатите» ке [5]. Развитие дефицита зрительнопространственной памяти у пациентов с различными стадиями НАЖБП было подтверждено в двух срезовых популяционных исследованиях и одном исследовании типа «случай-контроль» [4].…”
Section: результаты и их обсуждениеunclassified
“…Extensive evidence obtained in recent years has revealed that NAFLD could be linked to a lower cognitive performance [ 34 ], mood imbalances [ 35 ] (in particular, depression and anxiety), cerebrovascular alterations [ 36 ], and a low total cerebral volume [ 37 ]. When NAFLD develops, a number of pro-inflammatory cytokines and chemokines are released into the bloodstream, starting the coagulation cascade pathway and causing the endothelial dysfunction and cerebral atherosclerotic disease [ 38 , 39 , 40 , 41 ].…”
Section: Bile Acid Alterations and Their Function In Brain Diseasementioning
confidence: 99%